THE EFFECT OF USING COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TECHNIQUE ON SECONDARY SCHOOL STUDENTS’ READING COMPREHENSION - Aini, Nurul (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2024)
The aim of this research is to investigate whether or not the students who are taught by using CIRC technique get a better score than those who are not in reading comprehension achievement. It focused on answering general information and specific information question.CIRC is one of teaching technique which involves some students to predict, discuss and exchange ideas to solve the problems of the tasks given by the teacher. The researcher used quasi-experimental post test design only as a research design. The research participants were the tenth grade students in Mathematics and Natural Science class 2 and 3 at one of secondary school in Banyuwangi, Indonesia. The data of reading test was analyzed by using independent sample t-test through SPSS program. Homogeneity analysis indicated that the 2 groups/classes were homogenous (t=0.566>p=0.05). The method used for collecting data was test. The form of the test was multiple choices. Based on the data, it also was found the deviation for experimental group was 7.321 and control group was 7.296. After calculating the test scores, it was found the mean score for experimental group was 73.81 and for control group were 69.81. The data was calculated by using independent sample T-Test formula. The result of independent t-test was 0.021<0.05. It means that the null hypothesis (Ho) was rejected. It was proved that studying by using CIRC can give significant effect for students’ reading comprehension achievement. The teacher is suggested to use CIRC in order to increase the students’ reading comprehension achievement.